Apace: Dog Walking, Kinaesthetic Empathy, and Posthuman Ethos in the Great North Woods - McHugh, Susan (Humanimalia, 2024)
Researching nonfiction writing about where you call home is one way of appreciating conservation challenges. Living at the edge of the Great North Woods in Maine, I have found this work to be enriched by daily dog walks that cumulatively mark changes across time. Structured as a seasonal cycle, this essay ponders an idiosyncratic collection of evidence of more-than-human comings and goings, witnessed on two feet, accompanied by four more, in the first two decades of the twenty-first century. By writing about encounters with wildlife at close range, I reflect on specific ways in which my reading and dog walking practices together inspire extensions of empathy toward the ineffable relations that structure nature–culture borderlands. Becoming attuned to the critters within and without, betwixt and between house and home through extensions of kinaesthetic empathy, my hope is to model the development of a posthuman ethos through developing a storied appreciation for the elusive, unnamed intimacies of nonhuman neighbourliness that include, but are not limited to, witnessing dying and death.